Lecturer’ Strategies in Teaching Speaking on Online Learning During Pandemic Covid-19 - mike - amelia; Fitri Handayani (Journal of English Language Learning, 2021)
This study intends to investigate lecturers' practices for teaching speaking in online learning during pandemic COVID-19. For Lecturer, online learning has posed a new challenge, particularly in the area of teaching speaking. To make the lesson more exciting, the lecturer requires a strategy and should be able to mix it with online learning media. The research was descriptive qualitative study. The study focused on two UNSIKA-speaking lecturers. For the study, the researcher employed observation and interviews as instruments. According to the findings of the study, lecturers employ a variety of strategies to teach speaking, including podcasts, debates, and story-telling, retelling, dialogue, and drama. The lecturer combined some media in learning: whatsapp, zoom, microsof team, google meet, google classroom, youtube and edmodo.